LA REESTRUCTURACIÓN DE LAS ENTIDADES FINANCIERAS EN COLOMBIA: SITUACIONES QUE INCIDEN AL CAMBIO (2016)
The restructuring is a legal financial figure by which it seeks to transform, specialize, expand services, consolidate and rescue financial institutions that are in difficulties within the sector. To help you get the restructuring, the company must always have the approval of the Financial Superintendence of Colombia, overseer, controlling entity that will be responsible for giving the authorization, to join in the process if required, and may even work as a financial advice entity if institutions require it and / or request it.The article comes from the research project entitled: THE CONCEPT OF VALUE AND ITS IMPACT ON SECURITIZATION, project approved by the Research Center of Universidad Autonoma de las Americas, which has been working for almost five months, with the Group Ratio Juris, attached to Colciencias.In Colombia, we have many years developing of this kind of transformation, but the first that came to reality, were supported in the existing standard for the real sector, and the results were not good, also because some of these restructurings were made regardless the actual state of the financial institutions. We could conclude that there were many improvisations.Since the issuance of Decree 663 of 1993 (Organic Statute of the Financial System), the way of restructuring in Colombia has improved, given that the new rules are specific for the sector, and in that they identify the kinds of restructuring arranged for financial institutions, including: acquisition, merger, conversion, and transfer of assets, liabilities and contracts.In the last five years in the financial sector is showing significant movements through restructuring, especially in conversions, and of course many more are expected. This means that financial institutions are in constant search of new financial strategies, accommodations, and so on. This shows that activity in the sector due not only to the demands of a globalized industry and competitive zeal, but also driven by the growth of financial customers or users, as a response to the constant search for a thicker underground, between some other considerable issues.